What's in a Name: Elective Genealogy in Schwarz-Bart's Early Novels - Clarisse Zimra (Studies in 20th & 21st Century Literature, 1993)
This essay considers the question of the textual inscription of history in Solitude, Plat de porc and Télumée, by focusing on a narrative feature present in all three: the naming scene, wherein characters claim elective descent from a real historical figure, the pregnant mulatto woman, Solitude, captured and executed after the battle of Matouba in 1802 on Guadeloupe. Every Schwarz-Bart novel to date contains at least one scene, often several, staging this retelling of specifically Guadeloupean origins: the resistance to the reinstatement of slavery, and the ensuing tragedy on Matouba. In Un Plat de porc aux bananes vertes (1967), the child Mariotte, refusing the white values of her household, claims Solitude as model and ancestor. Later in Plule et vent sur Télumée Miracle (1972), Télumée regains her rightful place, through the connecting links of the oral chain, within a whole genealogy that is both biological and elective. Schwarz-Bart's corpus should be read as a gradual expansion of storytelling as a naming moment that makes sense of history in the retelling of it. This dramatized primal scene serves as matrix for the fictional discourse: it is the moment of revelation that simultaneously structures the narrator's individual consciousness and the narrative unfolding of a once-repressed collective memory. In the text's matricial moment, the daughter refuses the name—and the law—of the patriarchal Father (upending Lacan's "nom/non du père," so to speak) to reclaim the name, and, in Solitude's own pregnancy, the body of the Mother. It is a political act in that its coming into existence demands a radical shift in power relations as well as in consciousness. For a Schwarz-Bart heroine, this represents the first necessary step towards grounding herself in a tradition and an oral chain of her own choosing, with Negritude as its implied counter-text. What is remarkable is that Schwarz-Bart eventually rejects the binary, essentialist trap of male-oriented poetics, in order to arrive at a textual self-birthing fully aware of its polyvalent gender inflections. In claiming, and inscribing, Solitude as the Mother-Father of origins, Schwarz-Bart may well have snatched both Caliban and Caliban's sister away from Prospero's shadow.
Keywords: textual inscription; Solitude; Plat de porc; Télumée; mulatto; solitude; Schwarz-Bart; Guadeloupe; battle of Matouba; resistance; slavery; Un Plat de porc aux bananes vertes; Plule et vent sur Télumée Miracle; storytelling; memory; collective memory; power; power relations; consciousness; self-awareness; identity; family; family relations